2020
DOI: 10.1002/bin.1710
|View full text |Cite
|
Sign up to set email alerts
|

The effects of procedural integrity errors during auditory–visual conditional discrimination training: A preliminary investigation

Abstract: Procedural integrity errors have widespread implications for the success or failure of behavior analytic interventions. However, previous research has not examined the effects of procedural integrity errors during auditory-visual conditional discrimination with clinical populations. The purpose of this preliminary investigation was to replicate and extend the work of Carroll, Kodak, and Fisher by evaluating the effects of procedural integrity errors compared with perfect integrity during auditory-visual condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
(53 reference statements)
1
19
0
Order By: Relevance
“…Several descriptive studies reported that treatment‐integrity errors occur during instruction with consumers of applied behavior analysis (e.g., children with ASD; Brand et al, 2017; Breeman et al, 2020; Carroll et al, 2013; Kodak et al, 2018), but we cannot say whether the type and degree of errors evaluated in this translational study are likely to affect the acquisition of consumers like children with ASD in a similar way. Once additional studies have replicated our findings, future researchers should consider employing a parametric analysis of treatment integrity errors with individuals who are receiving behavior‐analytic skill‐acquisition intervention.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Several descriptive studies reported that treatment‐integrity errors occur during instruction with consumers of applied behavior analysis (e.g., children with ASD; Brand et al, 2017; Breeman et al, 2020; Carroll et al, 2013; Kodak et al, 2018), but we cannot say whether the type and degree of errors evaluated in this translational study are likely to affect the acquisition of consumers like children with ASD in a similar way. Once additional studies have replicated our findings, future researchers should consider employing a parametric analysis of treatment integrity errors with individuals who are receiving behavior‐analytic skill‐acquisition intervention.…”
Section: Discussionmentioning
confidence: 79%
“…Studies reviewed by Brand and colleagues contributed to the understanding of a functional relationship between reduced treatment integrity and ineffective or inefficient interventions (Fryling et al, 2012). Treatment‐integrity errors in the implementation of one or more components of behavior‐reduction and skill‐acquisition interventions result in poorer treatment outcomes (e.g., Bergmann et al, 2017; Breeman et al, 2020; Carroll et al, 2013; Jenkins et al, 2015; St. Peter Pipkin et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of isolated errors differed across participants, but the lowest levels of correct responses occurred in the condition with omissions of prompts. A similar analysis conducted by Breeman et al (2020) implemented errors in providing praise, delivering tangible items, and using an error‐correction procedure for 75% fidelity in DTI with two children with ASD, and the results replicated Carroll et al Participants acquired the skills more quickly with high‐fidelity instruction than reduced‐fidelity instruction.…”
Section: Procedural Fidelity As An Independent Variablementioning
confidence: 54%
“…Manipulating procedural fidelity as an IV has both practical and conceptual value (Vollmer et al, 1999). Practically, descriptive assessments show procedural‐fidelity errors can and do occur in the application of interventions based on the principles of behavior analysis (e.g., Brand et al, 2018; Breeman et al, 2020; Carroll et al, 2013; Donnelly & Karsten, 2017; Foreman et al, 2021; Kodak et al, 2018). Therefore, it is important that researchers understand the implications of procedural‐fidelity errors on behavior‐analytic interventions to analyze intervention efficacy and understand potential replication failures.…”
Section: Procedural Fidelity As An Independent Variablementioning
confidence: 99%